Transition from Spin Dewetting to continuous film in spin coating of Liquid Crystal 5CB - Dhara, Palash (Sci Rep, 2018)
Spin dewetting refers to spontaneous rupture of the dispensed solution layer during spin coating, resulting in isolated but periodic, regular sized domains of the solute and is pre-dominant when the solute concentration (C(n)) is very low. In this article we report how the morphology of liquid crystal (LC) 5CB thin films coated on flat and patterned PMMA substrate transform from spin dewetted droplets to continuous films with increase in C(n). We further show that within the spin dewetted regime, with gradual increase in the solute concentration, periodicity of the isotropic droplets (λ(D)) as well as their mean diameter (d(D)), gradually decreases, till the film becomes continuous at a critical concentration (C(n)*). Interestingly, the trend that λ(D) reduces with increase in C(n) is exact opposite to what is observed in thermal/solvent vapor induced dewetting of a thin film. The spin dewetted droplets exhibit transient Radial texture, in contrast to Schlieren texture observed in elongated threads and continuous films of 5CB, which remains in the Nematic phase at room temperature. Finally we show that by casting the film on a grating patterned substrate it becomes possible to align the spin dewetted droplets along the contours substrate patterns.